A Family–School Synergy Model for Enhancing Children’s Qur’anic Literacy: A Vygotskian Social Constructivist Perspective - Hilmy Yunan; Khozin; Rahmad Hakim (Journal of Teacher Training and Educational Research, 2026)
This study aims to develop a family–school synergy model for enhancing Qur’anic literacy among elementary school children through the Ummi method from Vygotsky’s social constructivist perspective. This research employed a library research method with a descriptive qualitative approach. Data were obtained from books, journal articles, official documents, and relevant scholarly literature on Qur’anic literacy, the Ummi method, family involvement, school–family collaboration, and Vygotsky’s social constructivism. The data were analyzed through data condensation, data display, conclusion drawing, and content analysis. The findings indicate that the Ummi method provides a structured foundation for Qur’anic learning through the principles of tartil, talaqqi, and ta’dib. Family involvement strengthens children’s Qur’anic literacy through home-based muraja’ah, motivation, religious modeling, and daily habituation. From a Vygotskian perspective, teachers and parents function as more knowledgeable others who provide scaffolding within children’s Zone of Proximal Development. The proposed model emphasizes school-based scaffolding, family-based scaffolding, collaborative scaffolding, and peer scaffolding as interconnected components in developing Qur’anic literacy. This study concludes that Qur’anic literacy should be designed as a collaborative learning ecosystem that integrates structured instruction, parental involvement, social interaction, and Qur’anic character formation.